Design challenges in contact plans for disruption-tolerant satellite networks - Fraire, Juan Andres (2015)
During the past 20 years, space communications technologies have shown limited progress in comparison to Internet-based networks on Earth. However, a brand new working group of the IETF with focus on DTN promises to extend today's Internet boundaries to embrace disruptive communications such as those seen in space networks. Nevertheless, several challenges need to be overcome before operative DTNs can be deployed in orbit. We analyze the state of the art of effective design, planning, and implementation of the forthcoming network communications opportunities (contacts). To this end, different modeling techniques, system constraints, selection criteria, and methods are reviewed and compared. Finally, we discuss the increasing complexity of considering routing and traffic information to enrich the planning procedure, yielding the need to implement a contact plan computation element to support space DTN operation.